(untitled) (Journal of Asian Development Studies, 2014)
The study examined the pattern of government expenditure in Nigeria to know if the growth of public expenditure follows the proposition of Wagner’s law of increasing state activities. The study utilized the Johansen cointegration test to examine data from 1960 to 2012. Government expenditure and gross domestic product was found to have long-run equilibrium relation with strong positive correlation as confirmation by correlation matrix. The findings supported the proposition of Wagner’s law of increasing state activities. Following the support for increasing state activities with increase in GDP, the government should endeavour that a larger fraction of the Gross National Expenditure be such that affect the real sector of the economy which will transmit to growth of the productive sector of the economy.